Stevin's 'Huysbou' (Bulletin KNOB, 1994)
Hendrik Stevin, Isaac Beeckman and Contantijn Huygens, each in their own way, showed various aspects of Stevin's Huvsbou. Hendrik tried to reconstruct the writings left to him into a theory and particularly emphasized his father's views on the layout of house and town. For Beeckman it was especially Stevin's pronouncements on the building practice that gave rise to further scientific reflections and experiments. Finally, Huygens introduced, on the one hand, Stevin's treatises on mechanics and technological developments in an international scientific debate; on the other hand, he included them in the theoretical basis of the description of his house as an illustration of the practical problems that had occurred while laying the foundation.It only presents a fragmentary image of Stevin's views on architecture and town planning; nevertheless, a number of general trends are to be recognized. In the first place, Stevin expresses extreme points of view in the field of the order of architecture. Although these points of view are extreme, they do link up with a debate on architectural theory that was fought out in the sixteenth and seventeenth centuries. His theory is further characterized by a practice-oriented scientific approach to architecture, expressed in a theoretical basis of technological developments as well as in giving concrete solutions to be used in the construction of the house and in the layout, maintenance and management of the town.In spite of the fact that Stevin's inventions were chiefly aimed at the situation in the Netherlands, the attention paid to mechanical and technical aspects of architecture are definitely not beyond the tradition of architectural theory of the sixteenth and seventeenth centuries. However, the fact that in international professional literature a one-sided interest developed in the design practice of Renaissance architecture and that in the Netherlands it is chiefly the passages on the five orders that have appeared in print, has had important consequences for the study of the relation between the architectural theory and the building practice in the Netherlands of the sixteenth and seventeenth centuries.These consequences are still to be seen in the more recent, conscientious studies of Terwen and Ottenheym in the stress they laid on proportions and measurements of their mathematical reconstructions of buildings of the Dutch Renaissance and Dutch Classicism; whereas in the significant contributions of Meischke and Zantkuijl the results of the developments in building and building technique have been highlighted in detail, among other things, from the point of view of conditions and restrictions such as the charters, but without making use of contemporary theoretical reflections on these developments.If we wish to bring these different approaches in architectural history closer together, a reconsideration of the relations between architectural theory and building practice is required. The notes from Huysbou by Stevin, Beeckman and Huygens, which betray a scientific approach to the practice of building, may form an important supplement to our knowledge of this relation. As we have seen, these notes are not unconnected, but as regards contents they seem to link up with the treatises on architecture of the sixteenth and seventeenth centuries. Not so much in the selective works that have appeared in print, but on the contrary, particularly in the incomplete texts inhandwriting.Paradoxically, the reconstruction of the few fragments of Huysbou and of the incomplete Dutch treatises on architecture can yield a much more complete image of the relation between the architectural theory and the building practice of the sixteenth and seventeenth centuries in the Netherlands.